10. PREVALANCE OF SURGICAL SITE INFECTION AND SOME RISK FACTORS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the rate of surgical site infection and associated factors at Thong Nhat Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 1601 patients who underwent clean or clean contaminated surgeries at Thong Nhat Hospital from February to June 2024. Data collected included gender, age, comorbidities, surgical history, ASA score, duration of surgery, wound classification, type of surgery, occurrence of surgical site infection, surgical site infection classification, and causative microorganisms.Results: The overall surgical site infection rate was 3.3%. Patients aged ≥ 60 had a 1.87-fold higher risk of surgical site infection (95% CI: 1.05-3.34) compared to those under 60. Patients with comorbidities were 2.09 times more likely to develop surgical site infections (95% CI: 1.18-3.69). An ASA score ≥ 3 increased the risk by 2.85 times (95% CI: 1.63-5.01). Surgery duration > 120 minutes was associated with a 2.31-fold increased risk (95% CI: 1.34-4.00). Clean contaminated wounds were nearly 2.94 times more likely to become infected than clean wounds (95% CI: 1.58-5.46).Conclusions: The overall surgical site infection rate was 3.3%. Statistically significant risk factors included: age ≥ 60 years, presence of comorbidities, ASA score ≥ 3, surgical duration > 120 minutes, and clean contaminated wound classification.
Keywords: Surgical site infection; ASA score; surgery; risk factors; infection control.